Creative accounting: a critical perspective. Literature Review - Mite Albán, María Teresa; Narváez Cumbicos, José Gonzalo; Cantos Lucas, Pablo Antonio; Andrade Garófalo, Carmen Aracely (Revista Universidad de Guayaquil, 2025)
Accounting has faced several challenges since its inception, one of the most important of which is the criteria for estimating and recording accounting. Although these criteria are essential for the autonomy of the accounting professional, they also represent a risk, as they can facilitate the manipulation of financial statements to benefit the company in the eyes of certain stakeholders. Despite the existence of Financial Reporting Standards, their flexibility can give rise to so-called “creative accounting”, where companies alter their economic presentation to attract investment and improve their financial position. This practice can compromise the quality and credibility of financial information, affecting both internal and external decision making. Globalization also influences this phenomenon, as it drives companies to become more competitive, which can lead to taking advantage of regulatory gaps. This study focuses on a bibliometric analysis of publications on creative accounting between 2010 and 2020, using scientific databases such as Scopus. Thirty articles were identified in high-impact journals that address this topic, highlighting that only three focus on publication trends. Based on these findings, it is recommended that more robust control methods be established to mitigate the negative effects of creative accounting and ensure that financial statements accurately reflect the economic reality of companies.